Migration routes and Bird Conservation Regions used by Eastern Population Tundra Swans Cygnus columbianus columbianus in North America - Wilkins, Khristi A; Malecki, Richard A; Sullivan, Patrick J; Fuller, Joseph C; Dunn, john P; Hindman, Larry J; Costanzo, Gary R; Luszcz, Dennis (Wildfowl, 2013)
The Eastern Population (EP) of Tundra Swans Cygnus columbianus columbianus breeds from the Alaskan North Slope to eastern Hudson Bay in Canada and winters in the eastern United States. Breeding and migration habitats have been difficult to identify because of the species’ vast and remote breeding range and its long-distance migration. A total of 43 female EP Tundra Swans were caught in Maryland, North Carolina, Pennsylvania and Virginia and marked with satellite transmitters to follow annual movements, delineate migration routes and determine Bird Conservation Region (BCR) use for EP Tundra Swans from November 2000–March 2002. Marked EP Tundra Swans spent approximately 3.5 months on breeding areas, 3.5 months on wintering areas and 5 months on staging areas, highlighting the importance of migratory habitats to these birds. Marked birds used 15 different ecologically distinct BCRs throughout the year: 10 during the spring, 11 during the autumn, four during the summer and six during the winter. The most important of these were the Prairie Potholes, Boreal Taiga Plains and Prairie Hardwood Transition during both spring and autumn; the Arctic Plains and Mountains during the summer; and the Mid-Atlantic coast during the winter. Fifty-five spring migration routes and 28 autumn routes used by marked birds were mapped. Seven sites were identified as being key migration staging areas that should be enhanced through habitat protection and management planning.